An evaluation of the impacts of culture-led industrial heritage regeneration projects in İstanbul - Şeren, Tuba Tellioğlu (İstanbul Bilgi Üniversitesi, 2019)
[Abstract Not Available]
İstanbul'daki kültür odaklı endüstriyel miras yenileme projelerinin etkilerine dair bir değerlendirme